G99(P) IVIG for Guillain-Barré syndrome: Which regimen should i choose?. (27th April 2016) - Ram, D; Aziz, M
Abstract : Aims: Guillain-Barré syndrome (GBS) is an autoimmune acute inflammatory polyradiculoneuropathy. Intravenous immunoglobulins (IVIG) are usually the first choice of treatment. At present, limited information is available regarding the most appropriate dosage regimen of IVIG in GBS. Common options used are 0.4gram/kg/day for 5 days or a single 2gram/kg dose. Our study aims to compare the clinical course and outcome between these two regimens. Methods: A retrospective 10 year analysis was performed. 32 children with GBS (median age of 5.7 years) who were admitted to our hospital between 2003 and 2013 were included in the review. Results: All children presented with ascending paralysis. The average time to maximum weakness from symptom onset was 6.5 days. 30 patients received IVIG, of which 16 children had 0.4g/kg/day for 5 days and 14 received a single dose of 2g/kg. IVIG was administered at a median time of 2 days from the onset of weakness in both cohorts. The mean disability grade on admission was similar in both groups. Children receiving treatment over 5 days had significantly shorter periods of mechanical ventilation and intensive care stay. Autonomic symptoms of GBS occurred more commonly in children who received a single dose (64%) compared to those who received it over 5 days (25%). 5 children (36%) in the 2g/kg group required a repeat IVIG dose due to deterioration in contrast to 1 child (6%) in the other cohort. The time to recovery from maximum weakness was quicker with the 5 day regimen (median 6 days) compared to the single dose regimen (median 8.5 days). The overall length of hospital stay was also shorter in the 0.4g/kg group. Conclusions: In children with GBS requiring IVIG, our study shows that administrating IVIG over 5 days is preferable, leading to faster recovery. It is also associated with a shorter duration spent in intensive care and in hospital on a whole. There were no differences noted in the long-term outcome of our patients from the use of either regimen.